ANALYSIS OF THE TAX BURDEN OF SMALL BUSINESS ENTITIES IN THE REPUBLIC OF UZBEKISTAN (World Economics and Finance Bulletin, 2025)
In the article, a study was conducted on determining the tax burden of small business entities. The level of tax burden of small business entities in the Republic of Uzbekistan was analyzed, the meth
Keywords: tax burden; tax analysis; tax burden level